PENGARUH KINERJA LINGKUNGAN DAN KEPEMILIKAN ASING TERHADAP KINERJA FINANSIAL PERUSAHAAN - Tita Djuitaningsih; Erista Eka Ristiawati (Universitas Jember, 2011)
This research aims to examine the effect of environmental performance and foreign ownership refer to financial performance in PROPER’s companies participant ,in cases where CSR Disclosure as a intervening variable. This study uses 34 samples of firms that listed as participant of Program Peringkat Kinerja Perusahaan Dalam Pengelolaan Lingkungan Hidup (PROPER) for the period of 2005 and 2007. Applying a partial least square method – PLS, this study found that environment performance has no effect to CSR Disclosure. Foreign ownership has an effect to CSR Disclosure. In other side, environmental performance and foreign ownership has and effect to return on assets one year ahead and return on equity one year ahead (ROAt+1 and ROEt+1), but they had no effect to company return (Rt+1) in one year ahead.The results of this study indicate that the CSR Disclosure can not be an intervening in the relationship between foreign ownership and environmental performance with financial performance. Keywords: environmental performance, PROPER, foreign ownership, financial performance, CSR Disclosure